Recent Research Mapping On The Effects Of Mango (Mangifera Indica L.) On Autoimmune Diseases: A Bibliometric Study - Afnizar Fawwaz; Nurhidayati Harun (Pharmacogenius Journal, 2026)
Introduction: Autoimmune diseases are characterized by dysregulated immune responses that result in chronic inflammation and progressive tissue damage. Mango (Mangifera indica) and its principal bioactive compound, mangiferin, have gained increasing scientific attention because of their immunomodulatory, anti-inflammatory, and antioxidant properties. However, the global research landscape regarding their potential role in autoimmune disease management has not yet been comprehensively mapped. Objectives: To present a bibliometric research mapping on the effects of mango fruit in the management of autoimmune diseases and to identify current research trends, emerging directions, and existing knowledge gaps. Methods: A data extraction table containing article metadata, including title, authors, publication year, journal, keywords, abstract, main topic, and relevance, was used as the research instrument. Literature was retrieved from PubMed, Scopus, and Web of Science using the keywords “mango and autoimmune” and “mangiferin and inflammation.” Eligible studies investigated the effects of mango fruit or its bioactive compounds on immune regulation and autoimmune diseases. Zotero was used for reference management, while VOSviewer and Biblioshiny were employed to analyze keyword co-occurrence, research trends, and author collaboration networks. Results: Bibliometric analysis revealed that the dominant keywords were “nonhuman,” “mouse,” “in vivo study,” and “drug efficacy,” indicating that current research is primarily based on experimental animal models. Cluster analysis identified immunological themes involving regulatory T lymphocytes, TH17 cells, and dendritic cells, alongside molecular pathways including NF-kappa B, antiapoptotic activity, and cell death, all associated with mangiferin-mediated immune regulation. Overlay visualization demonstrated that these immunological and molecular pathway-related keywords represent recent research hotspots. Although “mangiferin” was not a dominant keyword, its established association with these pathways highlights its potential as a promising therapeutic candidate for autoimmune disease management while emphasizing the need for further mechanistic and clinical investigations.